Variations in weed population densities, rate of change and community diversity in RR-soybeans and RR-maize strip crops under two herbicide strategies - Leguizamón, Eduardo S. (2012)
Concerns about the sustainability of large-scale, direct-drilled RR-soybeans (Glycine max), and RR-maize (Zea mays) under monoculture in central Argentina are growing steadily. An experiment was conducted during three consecutive years to determine the effects of crops and systems (monocultures and strips) and herbicide strategy on weed density, population rate of change (l), b community diversity (H́), crop yields and Land Equivalent Ratio (LER). Not only crops but also crop systems differentially influenced weed densities along their growth and development. For crop harvests, weed densities increased in both maize crop systems as compared to in the one for soybeans, but the lowest increase occurred in soybean strips. Differences were leveled by both herbicide strategies, which achieved 73% efficacy during the critical periods in both crops. l of annual monocotyledonous increased, thus shifting the weed community composition. Species richness and H́ were not affected by crop systems, but both herbicide strategies, particularly POST, either in soybeans in monoculture or in maize strips, significantly enhanced H́. Crop yields significantly increased in the maizestrip system with POST (Year 1) or PRE (Years 2 and 3) strategies, thus increasing LER above 1. Herbicide Environmental Load treatments fall within very low or low field use rating.